LCA of mobility solutions: approaches and findings—66th LCA forum, Swiss Federal Institute of Technology, Zurich, 30 August, 2017 - Mathys, Nicole (My University, 2018)
The presentations and discussions showed that the demand for transportation services will likely continue to grow substantially in the next decades. At the same time, the Paris Agreement requires a substantial reduction in greenhouse gas emissions to comply with the below 2 °C scenario or even the 1.5 °C scenario. In the past years, a lot of progress was made on the models on transportation and mobility, and the knowledge on the environmental impacts of the various transport modes substantially improved. However, the silver bullet for environmentally benign mobility seems not within reach in the coming years, and reducing the environmental impacts of mobility remains a technological and societal challenge.